Communication Skills Training at Sibanggede Village Cadets - Ida Bagus Gde Agung Yoga Pramana; Nuning Indah Pratiwi (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This community service is carried out by providing communication skills training to Karang Taruna in Sibanggede Village. Communication problems that occur due to misunderstandings between recipients of information and givers of information among Karang Taruna members need to be addressed in order to create effective communication and increase the productivity of the Sibanggede Village Karang Taruna organization. The methods used in this community service are training and education methods. The education provided is related to effective communication and organizational communication. The training provided is in the form of persuasive communication exercises using the role play method. This community service activity provides benefits for all members of the Sibanggede Village Youth Organization, namely increasing understanding and providing new skills in communicating between members of the organization and communicating with the village community.